2020
DOI: 10.1002/evl3.174
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic rate, context-dependent selection, and the competition-colonization trade-off

Abstract: Metabolism is linked with the pace-of-life, co-varying with survival, growth, and reproduction. Metabolic rates should therefore be under strong selection and, if heritable, become less variable over time. Yet intraspecific variation in metabolic rates is ubiquitous, even after accounting for body mass and temperature. Theory predicts variable selection maintains trait variation, but field estimates of how selection on metabolism varies are rare. We use a model marine invertebrate to estimate selection on meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 90 publications
(98 reference statements)
1
36
3
Order By: Relevance
“…Other studies have found strong selection on metabolic rate in our species (Pettersen et al 2016(Pettersen et al , 2020, whereas we did not. These differences may be due to the measurements of metabolic phenotypes at different life-history stages, which differ in the potential for the environment to affect metabolic rates (Withers et al 2006, White et al 2007, Jetz et al 2008, Alton et al 2012, Naya et al 2018.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Other studies have found strong selection on metabolic rate in our species (Pettersen et al 2016(Pettersen et al , 2020, whereas we did not. These differences may be due to the measurements of metabolic phenotypes at different life-history stages, which differ in the potential for the environment to affect metabolic rates (Withers et al 2006, White et al 2007, Jetz et al 2008, Alton et al 2012, Naya et al 2018.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, Pettersen et al (2016Pettersen et al ( , 2020 measured metabolic rates during the larval stage, whereas we determined metabolic rates of three weeks old colonies that had been in the field prior to measurements. Although metabolic rate is generally repeatable, especially over short timescales (White et al 2013), estimates of repeatability are usually lower under field conditions due to greater environmental variability (Auer et al 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers developed a simple model to describe the temperature dependence of developmental energet-ics in ectotherms that may provide insight into this phenomenon (Marshall et al, 2020;Pettersen et al, 2020). Under this model, the energetic cost of development is represented as the product of metabolic rate and incubation duration.…”
Section: Discussionmentioning
confidence: 99%
“…We gathered a total of 5,329 spatially explicit measurements of the physiological traits likely to dictate the responses of terrestrial animals to climate change: critical upper and lower thermal limits, supercooling temperature, optimal temperatures for performance, rates of metabolism, patterns of gas exchange and acclimation capacity (Table 1). The physiological traits we chose as means to identify studied environments define the range of temperatures over which animals can survive (critical upper and lower thermal limits, supercooling temperature), the rates at which they utilise energy and the demands they place on their environment (metabolic rate, which exhibits associations with survival and fitness that vary among environmental and ecological contexts: Boratyński & Koteja, 2009; Boyce et al., 2020; Pettersen et al., 2016, 2020), their susceptibility to desiccation stress (gas exchange patterns: Schimpf et al., 2012; White, Blackburn, Terblanche, et al., 2007), the temperatures at which functional performance (development, growth, and locomotion) is maximised, and their capacity to compensate physiologically for changes in the thermal environmental (acclimation capacity). The dataset includes records for 2,637 species, including insects, arachnids, fish, amphibians, reptiles, birds and mammals (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…supercooling temperature), the rates at which they utilise energy and the demands they place on their environment (metabolic rate, which exhibits associations with survival and fitness that vary among environmental and ecological contexts: Boratyński & Koteja, 2009;Boyce et al, 2020;Pettersen et al, 2016Pettersen et al, , 2020, their susceptibility to desiccation stress (gas exchange patterns: Schimpf et al, 2012;White, Blackburn, Terblanche, et al, 2007), the temperatures at which functional performance (development, growth, and locomotion) is maximised, and their capacity to compensate physiologically for changes in the thermal environmental (acclimation capacity). The dataset includes records for 2,637 species, including insects, arachnids, fish, amphibians, reptiles, birds and mammals (Table 1).…”
Section: Number Of Values Within 250 Kmmentioning
confidence: 99%